Histological and histopathological structural changes in the skin of the Basal Cells Carcinoma patients - Yassen Kadhim , Hala; Atta Ibrahim , Thekra; Hafedh Abbas, Ali (Diyala Journal of Medicine, 2024)
Background: Basal Cell Carcinoma (BCC) is the most common type of skin carcinoma and is considered an epidemic disease due to its increasing frequency in many countries. The most important problem of BCC is local invasion It grows in a “silent” way into immediately adjacent tissue. It rarely metastasizes. The early tumors are commonly small, translucent or pearly, raised and rounded areas located on a few dilated, superficial vessels. There are six subtypes of BCC that include nodular, pigmented, superficial, morphea form, cystic. The most important risk factor for basal cell carcinoma is exposure to UV-radiation. Outdoor workers with a long history of work-related UV-exposure are at increased risk of developing BCC. Other risk factors include family history of skin carcinoma, light skin phototypes, advanced age. Objective: The current study investigated pathological and histological changes in tissue sections to identify the factors contributing to the infection frequency. Patients and Methods: Thirty-three BCC patients' samples have been collected from the main care center at al-Baquba Teaching Hospital of Diyala Province, Iraq. All patient groups were clinically diagnosed as BCC by dermatologists. Results: The study showed macroscopic and microscopic histological changes. An ulcerated macroscopic appearance of the lesion was shown. The tumor lesions are located on the face. It was noted that the percentage of patients was higher in men than women and higher in light skin than dark skin. The study also showed that the age group 66-74 years had a higher infection percentage, while the lower percentage was of the age group > 83 years. Conclusion: These findings pave the way for future research endeavors aimed at prevention, early detection, and targeted treatment strategies for this prevalent skin carcinoma.